COMMITMENT TO THE PRINCIPLES OF SELF-PRESERVATION BEHAVIOR AMONG YOUTH: RESULTS AND PROBLEMS - Denisov, Aleksandr Pavlovich; Babenko, Anatoly Ivanovich; Denisova, Olga Alexandrovna; Filimonov, Sergey Nikolaevich (Medicine in Kuzbass, 2026)
Practical implementation of the principles of self-preservation behavior, as one of the main components of a healthy lifestyle, allows to preserve and strengthen health, to reveal individual potential. However, insufficient commitment of young people to these principles requires in-depth analysis and search for a solution to the problem, including with the help of social and hygienic investigation methods.The aim of the research was to study the commitment of contemporary youth to the principles of self-preservation behavior.Materials and methods. A questionnaire survey of students according to the author’s questionnaire was conducted. The Hospital Anxiety and Depression Scale was used to determine the level of mental comfort. Reported data on the consultation results at the Health Center were used.Results. It was found that the majority of young people (87.2%) understood the value of health and the role of a lifestyle in its ensuring and preserving. At the same time, insufficient readiness of the respondents to daily adherence to the principles of a healthy lifestyle was revealed. 78.4% of the respondents consumed alcoholic beverages, 61.0% of them smoked, 48.1% of the respondents practiced sports (or physical training), and 63.1% ate «regularly and sufficiently». Insufficient commitment to the principles of a healthy lifestyle against the background of an intensive educational process contributed to the onset of health problems in 19.4% of boys and 28.6% of girls (2 = 12.21; p = 0.025). Health Center data confirmed a fairly high tendency of young people to health-destroying behavior. Behavioral risk factors were identified in 52.3% of those examined.Conclusion. Self-preservation behavior among you this a multifaceted and complex problem, because the implementation of the principles of a healthy lifestyle is complicated by the insufficiently conscious attitude of young people to their own health. In this regard, the educational process should include activities to teach students the basic principles of self-preservation behavior, as well as to create incentives and conditions for their implementation.
Keywords: a healthy lifestyle; health status; principles of self-preservation behavior; bad habits